Energy every day - Woods, Ron , 1943 November 6-; Jordan, Chris , 1949- (Human Kinetics, 2010)
There's a worldwide energy crisis that has nothing to do with fossil fuels or nuclear and solar power. It's a crisis of personal energy. But this is one trend they don't have to accept. In fact, the solution is in their hands. This book shows how to incorporate physical activity into a daily routine for better health and increased energy